Tourism's contribution to the Philippine economy - Fernando, Krystelle Jade B.; Velasquez, Michaela Joy B.
This paper focuses on Tourisms' Contribution to the Philippine Economy. Tourism is categorized into three major activities which are leisure, business and those tourists who visit friends and relatives. Our study focuses mainly on leisure tourism activities which deal with the direct and indirect impact of tourism in the Philippine economy for both foreign and domestic. Tourism industries in the Philippines comprises of hotels for accommodations; restaurants and cafes; passenger transport or rail, road, water, and air services; travel agents; tour operators and tourism guide; transport equipment rental; recreation, entertainment, and cultural services; and retail trade for retail services. The positive impact of tourism can be seen not only with wealth generation and employment creation but also in the country's economic activity contributing to the Gross National Product (GNP), country's Balance of Payments (BOP), and creating opportunities. Benefits and problems from tourism effects economies, environment, cultures and the social interaction of communities htat persuade the fovernment, local areas, and commercial operators to invest in the industry and develop its full potential. The problems were given approapriate recommendations to further improve the prevailing conditions of tourism industry: (1) the government should urge to promote tourism hubs to further enhance accessibility of tourists' destinations. (2) the government should also promote the development and implementation of effective environmental strategies to fully develop primary toursits spots. Lastly, (3) the government should provide additional funds fot he construction and rehabilitation of other tourism scenic spots.